Musculoskeletal pain and physical functioning in the oldest old. (23rd August 2013) - Mänty, M.; Thinggaard, M.; Christensen, K.; Avlund, K.
Abstract Background Little is known about the impact of pain on physical functioning among the oldest‐old subjects. In this study, we first examined the associations between the number of painful sites and measures of physical functioning reflecting different stages of the disablement process (physical impairment, functional limitation and disability) among nonagenarians (more than ninety years old persons). Second, we described the effect of painful sites on disability during a 2‐year follow‐up period. Methods This study is based on baseline (n = 1177) and 2‐year follow‐up (n = 709) data of the nationwide Danish 1905 cohort study. Musculoskeletal pain was assessed as reported pain in back, hips or knees when moving or resting. Physical performance measures included maximum grip strength and habitual walking speed. Disability in performing activities of daily living was defined as the need for assistive device or personal help in transferring, dressing, washing, using toilet and/or walking indoors. Results At baseline, the number of painful sites was significantly associated with measured grip strength and walking speed as well as self‐reported disability in a stepwise manner; the more sites with pain, the poorer the physical functioning. The follow‐up analyses showed corresponding but slightly weaker stepwise associations between baseline pain and disability level at follow‐up, and indicated that although on the whole, single or multi‐site pain did not predict the onset of disability, multi‐site pain increased the risk of developing severe disability. Conclusions The findings of this study suggest that musculoskeletal pain in nonagenarians is highly prevalent and is associated with poor physical performance and disability.